Influencing Factors Analysis of Marine Tourism Demand in the Sanggar Beach Area, Tulungagung - Amalia Febryane Adhani Mazaya; Fitriana Wulan Ramadhani; Anissa Aprilia Nurkhasanah; Mentari Puspa Wardani (Jurnal Media Akuakultur Indonesia, 2025)
Sanggar Beach in Tulungagung Regency has marine tourism potential based on its natural landscape, coastal beauty, and green turtle conservation value. However, limited accessibility, basic facilities, and safety risks hinder increasing tourism demand. This background necessitates a study of the factors influencing tourist interest. The purpose of this study is to analyze the variables influencing tourism demand to Sanggar Beach and formulate recommendations for sustainable destination management strategies. The research method was conducted through a field survey, interviews, and questionnaires distributed to 30 tourists using a purposive sampling technique. Data were analyzed quantitatively using multiple linear regression, complemented by descriptive analysis of tourist characteristics and the condition of attractions, accessibility, and amenities. The results indicate that the majority of tourists are young (15–25 years old), have a high school or bachelor's degree, have low to middle incomes, and are predominantly private sector workers and students. The regression analysis showed a very strong relationship (R = 0.90) with an R² = 0.80, meaning that 80% of the variation in tourism demand can be explained by the research variables. Simultaneously, independent variables significantly influence demand, although partially no significant effect was found at the 5% level, except for age, which approached significance (p = 0.0531). Facility evaluations show that attractions are excellent, the turtle hatchery is quite good, road access is considered poor, while amenities are mostly adequate but need improvement, especially the gazebo. In conclusion, tourism demand to Sanggar Beach is influenced by demographic factors and destination quality, with accessibility and facilities as the aspects that need the most improvement. Strategies to strengthen attractions, improve infrastructure, and improve amenities will support sustainable tourism growth.